PUSHOVER ANALYSIS ON A MOSQUE BUILDING STRUCTURE WITH A TIERED ROOF SLAB - Pandiangan, Naek Rizki; Pratiwi, Ade Yuniati (Universitas Lambung Mangkurat, 2026)
Damage to building structures poses a threat to the quality of the building, which will impact its functionality. Structural damage can be caused by earthquakes. This research aims to determine the performance level and the effect of variations in short column heights on the inter-story drift of a mosque building with a tiered roof slab in a pushover analysis. The pushover analysis in this study refers to FEMA 356 and ATC-40, by determining the target displacement value, drift ratio, collapse mechanism, and building performance level. In accordance with FEMA 356, the pushover analysis results show an Operational performance level with drift ratios in the X and Y directions of 0.451% and 0.458% respectively, which means the building only experienced minor damage and can still be used as normal. Based on ATC-40, the analysis results show an Immediate Occupancy performance with a drift ratio in the X and Y directions of 0.00368, so the building is in a safe condition and can be used immediately. The influence of variations in column height on inter-story drift shows that the higher the column, the larger the inter-story drift.Keywords : Pushover Analysis, Target Displacement, Drift Ratio, Plastic Hinge, Performance Level, Tiered Roof Slab